Tensimeter Digital Berbasis Arduino Dengan Transfer Data Berbasis Android Melalui Bluetooth - TANJUNG, SHOLIHUDIN DWI PRIHATONO, Ratnasari N R, S.T.,M.T (2017)
Tensimeter an instrument for measuring blood pressure are often used in the medical world. Its function is vital because it is the basic for doctors to diagnose the patient's current health check-up. tensimeter generally divided into two, that is analog and digital Tensimeter. In the modern period right now, Android smartphones already developed with all features which very sophisticated. Because of it makes the author want to create a instrument digital Tensimeter that is integrated with android using Arduino Uno as a microcontroller. The method used in this research was experiment. To be able to detect the blood pressure values,so used a MPX5050dp sensors that will change the pressure value into voltage, then the value will be processed by a microcontroller to determine the value of systole and diastole. After the systolic and diastolic values obtained then the results will be displayed on the LCD screen located on the instrument and also transferred to the smartphone's display on the screen the application via bluetooth HC-05. The results pf experiment is the percentage error equal to 2.06% for systole and diastole is the percentage error of 9.3%. Arduino Tensimeters can work well when the patient is in a relaxed condition. Keywords: Arduino Uno, Bluetooth HC-05, Sensor MPX5050dp, Microcontroller.